2014
DOI: 10.1016/j.jbiomech.2013.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Development and experimental validation of a finite element model of total ankle replacement

Abstract: a b s t r a c tTotal ankle replacement remains a less satisfactory solution compared to other joint replacements. The goal of this study was to develop and validate a finite element model of total ankle replacement, for future testing of hypotheses related to clinical issues. To validate the finite element model, an experimental setup was specifically developed and applied on 8 cadaveric tibias. A non-cemented press fit tibial component of a mobile bearing prosthesis was inserted into the tibias. Two extreme a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 16 publications
1
24
1
Order By: Relevance
“…Finally, unequal dispersion of the load about the subarticular bone adjacent to the metallic prosthesis components could be responsible for aseptic osteolysis and loosening. Specifically, the location of osteolysis concentrated around the tibial keel and conical fixation plug for the Salto Ò mobile version prosthesis correlates exactly with the increased load transmission and strain during thermoelastic stress analysis (71) and finite element modeling (72). Therefore, additional refinement of the tibial component to redistribute stress for more even dispersion of load should be an area of future study.…”
Section: Discussionmentioning
confidence: 86%
“…Finally, unequal dispersion of the load about the subarticular bone adjacent to the metallic prosthesis components could be responsible for aseptic osteolysis and loosening. Specifically, the location of osteolysis concentrated around the tibial keel and conical fixation plug for the Salto Ò mobile version prosthesis correlates exactly with the increased load transmission and strain during thermoelastic stress analysis (71) and finite element modeling (72). Therefore, additional refinement of the tibial component to redistribute stress for more even dispersion of load should be an area of future study.…”
Section: Discussionmentioning
confidence: 86%
“…hip, [14], [15]; shoulder, [16], [17], [18]). Several studies have employed FEM to explore the performance of current TAR devices: Terrier et al [19], [20], [21] modelled the Salto ® implanted in the tibia to explore bone strains and stresses occurring at the implant vicinity. Espinosa et al [22] developed a model to study contact pressures occurring in the PE component of the Agility ® and Mobility ® .…”
Section: Introductionmentioning
confidence: 99%
“…Using a validated finite element model (Terrier et al 2014), we compared both Salto mobile bearing and Salto Talaris fixed bearing prosthesis types. Based on seven tibias, our results showed that there are no significant differences in critical bone strain and bone-implant interface stress between the two prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative analysis was performed on seven finite element models, built and validated from seven cadaveric tibias (Terrier et al 2014). All tibias were segmented from CT images, using the imaging software Amira (FEI Visualization Sciences Group, Bordeaux, France).…”
Section: Methodsmentioning
confidence: 99%